VIRTUAL COMPETITIVENESS: YOUTHS’ VIEWS - M. Yu. Semenov (Образование и наука)
Introduction. Nowadays, the use of information and communication technologies (ICT) has become an integral part both of every individual’s life and of the society in general. It is no longer possible to deny the impact of virtual environment on socialisation and development of the identity of young people. In this regard, the investigation of young people’s view on virtual social networks, and the possibility of students’ own competitiveness realization through various web services. The aim of the research presented in the article is to study the factors of students’ assessment of virtual social networks as a tool of personal fulfillment. Methodology and research methods. Content analysis and synthesis of scientific publications studies were carried out at a theoretical stage of the research; secondary sampling analysis of sociologic data material sources was conducted. The empirical research stage involved the instrument of questionnaire surveys, statistical data processing and interpretation of the results. Results and scientific novelty. The social survey conducted in 2017 with the participation of 1087 high school students and 1196 college students of the Tyumen Region shown that the more competitive students consider themselves, the more competitive they perceive the people having great popularity on the Internet. At that, compared to girls, young people are more inclined to consider the people having great popularity on the Internet competitive. It is determined that having a popular virtual media account for the young person is less worthwhile than for female respondents. The author explains this fact: male representatives regard it as “social capital” which can contribute to growth of their competitiveness in society as well as to achieve some profit. The author concludes that youth views on competitiveness are not directly related to the activity in virtual social networks. Frequent use by respondents of the Internet and ICTs both in the course of training, and in spare time does not depend on the perception of personal level of competitiveness in society; although, the importance of having own popular social media account on the Internet is directly proportional to the level of own competitiveness assessment. Practical significance. The materials of the present research can be applied to develop and design recommendations for psychological and pedagogical maintenance of the process of youth socialization.